Legitimacy Principle of Equality in Collection of Rural and Urban Land Tax - Ayuningsekar, Cahya Intan; Jaelani, Abdul Kadir; Hermawan, Sapto (Lembaga Contrarius Indonesia, 2023)
This study aims to examine the application of the principle of equality in the collection of Rural and Urban Land and Building Tax in Magelang City and identify the factors that affect the sustainability of the collection of Rural and Urban Land and Building Tax in Magelang City. This research uses a normative research method by applying a conceptual approach to the writing process. As a result, the implementation of Rural and Urban Land and Building Tax collection in Magelang City has not illustrated the optimal performance of the principle of Equality. This can be seen from several aspects, such as the implementation of services for taxpayers between villages that are not the same as those carried out by the tax authorities, proportional rates that are too flat for each taxpayer, and no explanation of the boundaries or elements that become the benchmark for a taxpayer to be said to have low income and be entitled to a tax reduction. As for its implementation, the collection of Rural and Urban Land and Building Tax in Magelang City is influenced by several factors, population, per capita income, economic inflation rate, taxpayer knowledge factor, tax collection method factor, tax benefit factor, third party role effectiveness factor, taxpayer compliance factor, tax e-system factor, continuous socialization factor, and complete regulation factor.